Unprecedented toughening high-performance polyhexahydrotriazines constructed by incorporating point–face cation–π interactions in covalently crosslinked networks and the visual detection of tensile strength. Issue 7 (23rd December 2019) - Guan, Xiaofang; Ma, Yuanchi; Yang, Li; Xu, Yewei; Lan, Yang; Huang, Ying; Philas Diangha, Tasah; Chang, Guanjun
Abstract : We described a new concept for the design of high-performance supramolecular thermosets by incorporating point–face cation–π interactions in covalently crosslinked networks. Abstract : We described a new concept for the design of high-performance supramolecular thermosets by incorporating point–face cation–π interactions in covalently crosslinked networks. Our findings showed an unprecedented increase in tensile strength and extensibility at once, a previously unknown behavior for stiff high performance polymers.